Tree-grass interactions for N in Nothofagus antarctica silvopastoral systems: evidence of facilitation from trees to underneath grasses - Gargaglione, Veronica Beatriz; Peri, Pablo Luis; Rubio, Gerardo (Agroforestry Systems)
Nothofagus antarctica forests in south Patagonia are usually used as silvopastoral systems but how grasses and trees compete for specific resources, such as nitrogen in these systems is unknown. To understand interactions between grasses and N. antarctica trees for N, an experiment with 15N labeled fertilizer was carried out comparing N absorption by grasses growing under trees (silvopastoral system) with an open site. Labeled 15NH415NO3 fertilizer at 10 % atom excess was added in spring at both sites and 15N was measured in herbage, soil and trees every 30 days during the growing season. Soil was the component that containing the greatest amount of N and greatest 15N recovery. Grasses growing in the silvopastoral system absorbed almost double of the fertilizer applied than grasses in the open site (32.4 kg N ha−1derived from fertilizer based on 15N recovery). Roots were also an important fate for N absorbed, representing 50 and 63 % of total 15N recovered in grass roots of open and silvopastoral sites, respectively. Trees absorbed 69 % less applied N than grasses in the silvopastoral system; being mainly allocated in small branches, sapwood and fine roots. Overall, 15N recovery was 65 % higher in the silvopastoral system (tree + grasses) than in the open site (grasses). Silvopastoral system made more efficient use of the 15N added. These results indicated that N. antarctica trees in the silvopastoral system may “facilitate” fertilizer N absorption of grasses by improving environmental conditions like water availability or by reducing competition for inorganic N between soil microorganisms and plants. Fil: Gargaglione, Veronica Beatriz. Universidad Nacional de la Patagonia Austral; Argentina. Instituto Nacional de Tecnología Agropecuaria. Estación Experimental Santa Cruz; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral; Argentina. Instituto Nacional de Tecnología Agropecuaria. Estación Experimental Santa ...